DINAMIKA DALAM PENERAPAN SISTEM PEMERINTAHAN PESIDENSIAL DAN PARLEMENTER DI INDONESIA - Muhammad Taufik (Qaumiyyah: Jurnal Hukum Tata Negara, 2020)
The implementation of democracy in each country takes different forms between one country and another, sometimes in a country in carrying out democracy it takes the form of a parliamentary system, likewise sometimes a country runs a presidential system in order to realize democracy. Meanwhile, in the context of the Indonesian state, the implementation of a government system whether it uses a presidential or parliamentary system is still a dynamic and debate until now among experts in constitutional law and politics that the Indonesian government system adopts what form of government system. Some experts have argued that when the 1945 Constitution had not been amended, the style of Indonesian government was often said to be a semi-presidential system. However, in practice the Indonesian government system is closer to a parliamentary style as was the case during the constitution of the Republic of the United States of Indonesia (RIS) and the UUDS in 1950, and after the amendments to the 1945 Constitution, the Indonesian government system became a pure presidential system. Several other experts stated that the Indonesian government system adopted a presidential system of government because it was of the opinion that the president's accountability to the MPR was not the responsibility of the legislative body. In this case he added, the President's accountability to the MPR should not be equated with a cabinet's accountability to parliament (in the parliamentary system). Therefore, it is very important to trace the implementation of the government system in Indonesia to date, whether it is adopting a pure presidential system or a mixture of presidential and parliamentary systems. Abstrak Implementasi demokrasi dalam setiap negara mengambil bentuk yang berbeda-beda antara negara yang satu maupun negara lain, terkadang dalam sebuah negara dalam menjalankan demokrasi mengambil bentuk sistem parlementer, demikian pula terkadang suatu negara menjalankan sistem presidensial demi untuk mewujudkan demokrasi. Sementara dalam konteks negara Indonesia, penerapan sistem pemerintahan apakah menggunakan sistem presindesial atau parlementer masih menjadi suatu dinamika dan perdebatan sampai sekarang dikalangan para pakar hukum tata negara dan politik bahwa sistem pemerintahan Indonesia menganut sistem pemerintahan yang berbentuk apa. Beberapa pakar mengemukakan bahwa ketika UUD 1945 belum diamandemen, corak pemerintahan Indonesia sering dikatakan sebagai sistem semi presidensial. Namun dalam prakteknya sistem pemerintahan Indonesia justru lebih mendekati corak parlementer seperti halnya dalam masa konstitusi Republik Indonesia Serikat (RIS) dan UUDS tahun 1950, dan setelah amandemen UUD 1945 sistem pemerintahan Indonesia menjadi sistem presidnesial murni. Beberapa pakar lain menyebutkan bahwa sistem pemerintahan Indonesia menganut sistem pemerintahan presidensial karena berpendapat pertanggungjawaban presiden kepada MPR bukan merupakan pertanggungjawaban kepada badan legeslatif. dalam hal ini menambahkan, petanggungjawaban Presiden kepada MPR tidak boleh disamakan dengan pertanggungjawaban kabinet kepada parlemen (dalam sistem parlementer). Karena itu, menjadi hal sangat penting untuk menelusuri pelaksanaan sistem pemerintahan di Indonesia hingga sekarang ini, apakah menganut sistem presidensial murni atau campuran sistem presidensial dan parlementer.